Surface Magneto-Optic Kerr Effect in Permalloy thin films (Ni81 Fe19) - Gutarra, Abel (2008)
A surface Kerr effect magnetometer (MEKS) was built to measure the magnetic properties of Permalloy (Ni81Fe19) thin films of 20 nm thickness. It was found that the coercive field of the samples has values between 2-6 Oe. The films showed in-plane uniaxial anisotropy and axes of easy and difficult magnetization were identified. The Kerr angle was measured for the longitudinal and polar configurations and the magnetic saturation for different angles of incidence of the light beam. The results were satisfactorily compared with those obtained with a Vibrating Sample Magnetometer (VSM).